Could uric acid to high-density lipoprotein cholesterol ratio be used to predict late-stage saphenous vein graft disease after coronary artery bypass graft surgery? - Güvenç, Orhan; Engin, Mesut; Demir, Ömer Furkan; Ata, Filiz; Yavuz, Senol (The European Research Journal, 2023)
Objectives: Various vascular grafts are used in coronary artery bypass graft (CABG) surgeries, however, the most commonly used one is the saphenous vein graft (SVG). Various studies conducted on this topic have found a relationship between uric acid to HDL-C (UHR) and cardiovascular diseases. In this current study, we aimed to investigate the predictive importance of UHR value in predicting long-term SVG disease in patients who underwent CABG surgery. Methods: Patients who had a history of CABG surgery at least one year prior, had stable angina pectoris, and underwent coronary angiography between January 01, 2016 and January 01, 2020, were included in the study retrospectively. Patients with open saphenous veins were defined as Group 1, and patients who had 50% or more stenosis in at least one SVG after coronary angiography, were defined as Group 2. Results: The median age of the 204 patients included in Group 1 and 292 patients in Group 2 were 65 (38-77) years and 66 (45-79) years, respectively (p = 0.251). The two groups were similar in terms of gender, hypertension, chronic obstructive pulmonary disease rates, history of cerebrovascular events, ejection fraction, body mass index, and current medical treatments. In univariate analysis, SVG disease was found to significantly correlate with diabeter mellitus (odds ratio [OR]: 1.644, 95% confidence interval [CI]: 1.190-1.985, p = 0.008), current smoking (OR: 0.875, 95% CI: 0.669-0.940, p = 0.030), number of patients with target artery diameter < 1.5 mm (OR: 1.945, 95% CI: 1.221-2.398, p < 0.001), age of SVG (OR: 2.960, 95% CI: 1.980-4.168, p < 0.001), uric acid (OR: 1.241, 95% CI: 1.078-1.592, p = 0.004), triglyceride (OR: 0.780, 95% CI: 0.569-0.935, p = 0.044) and UHR (OR: 1.894, 95% CI: 1.384-2.896, p < 0.001). Conclusions: In this study, we showed that we can predict saphenous vein graft occlusion with serum UHR value.